Power system generation: current trend towards sustainable energy storage systems - Razali, Mohd Najib; Mahmud, Mohd Sabri; Syahirah Syazwani, Syahirah Syazwani; Tarmizi, Mohd; Mohd Zuhan, Mohd Khairul Nizam
Nowadays, our country needs to revise the usage of energy resources in every sector. This generally will affect our economy as well as our environment. Renewable energy has been debated to protect our Earth towards a bright future. Many types of renewable energy should be taken into consideration, along with rechargeable energy. Rechargeable energy seems to be a better option to lower carbon emissions. The battery is one of the chemicals that is frequently used in many indus-tries to supply energy in terms of electrical energy. The trend towards sustainable energy storage systems was studied as the prevention of any pollution in this world